The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.31744/einstein_journal/2022ao6553
|View full text |Cite
|
Sign up to set email alerts
|

Increase in direct costs for health systems due to lupus nephritis: the case of Colombia

Abstract: Objective: Lupus nephritis is one of the most severe complications of systemic lupus erythematosus and it has been estimated that can occur in up to 60% of patients. Direct costs of lupus nephritis have not been studied in developing countries. This study aimed to describe lupus nephritis direct costs in Colombia. Methods: Administrative data from two Colombian health maintenance organizations for 2014 and 2015 was obtained. An algorithm based on the International Statistical Classification of Diseases and Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…[6][7][8][9][10]31,32 Specially, patients with lupus nephritis contribute to a major economic burden comparing with lupus without nephritis. [11][12][13][14]33 Cumulative damage (highest SDI 34 scores) has also been described as a factor of increased disease costs, showing 10-year cumulative costs 9-fold higher than those with lower damage. 35 Data regarding economic burden of SLE are mainly from developed countries with scarce data from other countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9][10]31,32 Specially, patients with lupus nephritis contribute to a major economic burden comparing with lupus without nephritis. [11][12][13][14]33 Cumulative damage (highest SDI 34 scores) has also been described as a factor of increased disease costs, showing 10-year cumulative costs 9-fold higher than those with lower damage. 35 Data regarding economic burden of SLE are mainly from developed countries with scarce data from other countries.…”
Section: Discussionmentioning
confidence: 99%
“…32 Also in Colombia, annual costs for patients with lupus nephritis have been calculated to be 7.46 times greater than those without nephritis. 13 As far as we know, up to date there is no other data on SLE health care resource use from other Latin American countries and no data from Argentina. 46.4 (17.9) Follow-up time, years, median (IQR) 8.0 (5.0-12.4) Fulfilling 1997 ACR lupus criteria 23 , n (%) 46 (74.2) Fulfilling SLICC lupus criteria 24 , n (%) 62 (100) Charlson a score at diagnosis, median (IQR) 0 (0-2) Charlson a score at the end of follow-up, median (IQR) 1 (0-3) SLICC damage index score at the end of follow-up, median (IQR) 0 (0-2) Death, n (%) We found in our cohort that patients experienced the majority of the follow-up in a remission state (74.4% of the time), and the median time on remission was 62.5 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average annual per-patient, all-claims, all-cause direct cost for LN was 12,624 dollars, 7.5 times higher than the average lupus patient without LN. 27 Early diagnosis and proper treatment are important to control LN progression, especially preventing ESRD. 28 The reported improvements of LN outcomes have been attributed to earlier diagnosis and optimal management in European patients over the past decade.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, southern sub-Saharan Africa (10.5%) and the group of Latin American countries aforementioned (7.7%) showed increasing trends in age-standardized point/prevalence estimates between 1990 and 2017. A Colombian study found that patients with SLE who developed lupus nephritis had a 7-fold increase in mean annual direct costs per patient for the health system in that country compared with patients without it [ 29 ]. The overall average annual direct cost per patient has been calculated around 2355 US dollars (USD) in Colombia, while for HICs, the mean annual direct costs per patient ranged from 2214 to 16 875 USD [ 30 ].…”
Section: Specific Challenges To Lmic Healthcare Systemsmentioning
confidence: 99%